Analysis of factors affecting inflation in Vietnam during the COVID-19 pandemic - Mai, Thu Hien; Le, Thuy Linh (Journal of International Economics and Management, 2024)
During the COVID-19 pandemic, countries have faced various economic repercussions, including high inflation rates. By employing the autoregressive distributed lag approach and autoregressive distributed lag bounds test, this study aims to estimate the impact of macroeconomic factors and the factors related to COVID-19 on inflation in Vietnam from 2020 to 2022. The results show that both in the short and long term, factors such as FDI, short-term interbank interest rates, oil price index, real exchange rate, and import prices increase the inflation rate. By contrast, freight and carriage reduce inflation. Although the industrial production index has a negative impact in the short run, this impact is insignificant in the long term. The number of deaths, on the other hand, only has a positive impact on inflation in the long run. The findings of this study provide a foundation for future research seeking to expand the scope of factors influencing inflation. Additionally, this paper proposes recommendations to control inflation in Vietnam in the context of resuming economic activities after the pandemic.